The reasonable time in the Peruvian Constitutional Court's extradition case law - Estrada Bravo, Anyela Maria (2024)
Based on an analysis of the jurisprudence of the Constitutional Court, the purpose of this article is to evaluate the extent to which the Peruvian interpreter has incorporated the observations of the Inter-American Court of Human Rights regarding the guarantee of reasonable time in extradition proceedings. The starting point for this evaluation is the Won Ho Wing case, in which, although the IACHR Court did not determine the responsibility of the Peruvian State with respect to its obligations of non-refoulement due to the risk against the rights to life and personal integrity, it did point out that it was internationally responsible for violating the guarantee of reasonable time.